Analisis Strategi Penetapan Tarif Pelayanan Pasien Cerebro Vascular Accident (CVA) Infark Menggunakan Metode Time Driven Activity Based Costing: Studi Kualitatif di Rumah Sakit Wava Husada Malang - Risa Qohardita; Rian Andriani; Dadang Kusnadi (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
Hospitals are complex organizations because they have two functions, namely as social units and profit units, in the BPJS era hospitals in Indonesia face various challenges, one of which is that the number of INACBGs claims is smaller than the hospital's operational costs. Stroke is a catastrophic disease that has serious life-threatening complications, requires intensive care long-term care, and also requires high financing. Currently, hospitals in Indonesia, especially Wava Husada Hospital, still use an inefficient and inaccurate administrative process where the determination of hospital rates still uses a conventional system. The TD ABC method can be used to support cost transparency, increase profitability, and generate more accurate unit costs. This study uses a qualitative research design with a case study type, the research object of this study is the unit cost of service for CVA Infarction patients without complications from the time the patient is admitted to the emergency room until the patient returns home from the stroke installation. analyzed using cost benefit analysis (NPV, IRR, PBP, and PI). The total unit cost is Rp 4,807,638.43. Payback Period 6 years 4 months 11 days, Profitability Index is not worth continuing because it is worth < 1, Net Present Value -Rp3,199,846,858.00 (Negative), NPV is not financially feasible because it still suffers losses, Internal Rate of Return with an internal rate of return from an investment of 2.71% (Low). The basic rate of Wava Husada Hospital for the service of one patient with CVA infarction without complications is Rp5,268,151, while with the TD ABC method the cost incurred for one patient is Rp4,807,638.43 with a difference of Rp460,512.57.